Pendekatan Filosofis dan Ilmiah dalam Memahami Manusia dan Pengetahuan: Implikasinya terhadap Pendidikan Jasmani Holistik - Aswar, Muh; Farrel, Aura; Putra, Senja Ariya; Carsiwan, Carsiwan (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This article explores philosophical approaches in understanding human nature and knowledge and examines their implications for holistic physical education. This study analyzes literature from various related disciplines, such as philosophy and education, through a comprehensive literature review. From a philosophical perspective, this study examines key concepts such as basic human nature, human potential, and the role of physical activity in the overall development of individuals. In addition, this study also examines how humans acquire knowledge through experience and learning. By integrating insights from multiple sources, the study offers a powerful synthesis of the implications of philosophical approaches to holistic physical education. The main implications discussed include setting goals and values of physical education that are in line with basic human nature, the development of teaching strategies that are appropriate to the way humans learn, and the integration of physical, cognitive, and affective aspects in the learning process. In addition, the study also highlights the importance of an interdisciplinary approach in physical education. Keywords: Human nature, Holistic physical education, Individual development, Interdisciplinary, Philosophical approach This article explores philosophical approaches in understanding human nature and knowledge and examines their implications for holistic physical education. This study analyzes literature from various related disciplines, such as philosophy and education, through a comprehensive literature review. From a philosophical perspective, this study examines key concepts such as basic human nature, human potential, and the role of physical activity in the overall development of individuals. In addition, this study also examines how humans acquire knowledge through experience and learning. By integrating insights from multiple sources, the study offers a powerful synthesis of the implications of philosophical approaches to holistic physical education. The main implications discussed include setting goals and values of physical education that are in line with basic human nature, the development of teaching strategies that are appropriate to the way humans learn, and the integration of physical, cognitive, and affective aspects in the learning process. In addition, the study also highlights the importance of an interdisciplinary approach in physical education. Keywords: Human nature, Holistic physical education, Individual development, Interdisciplinary, Philosophical approach